(untitled) (Scientific journal of the Fergana State University, 2024)
Pine hermes (Pinus strobi Hartig, 1839) is a widespread species in the Fergana Valley. Dendrotamnobiont. Narrow oligophage. Among the pines, P. silvestris and P. pallasiana dominate. In the city of Fergana it occurs from midspring to late autumn. Rapid mass reproduction.